Grinding characteristics of waste printed circuit boards in hammer mill using population balance model. Issue 4 (4th July 2021) - Lee, Wonjae; Park, Seungsoo; Park, Jaikoo
ABSTRACT: In this study, the grinding characteristics of waste printed circuit boards (PCBs) were evaluated using a population balance model (PBM). The grinding characteristics under various conditions (hammer rotational speeds of 1600, 2000, and 2400 rpm; screen aperture sizes of 0.71, 1.0, and 1.40 mm; and maximum feed sizes of 4, 6, and 8 mm) were identified. A PBM for a continuous hammer mill was used to quantitatively demonstrate the grinding characteristics. No significant difference was observed in the particle sizes of the products for various hammer rotational speeds. Nevertheless, the specific rate of breakage increased with the hammer rotational speed. As expected, a narrow screen aperture yielded a fine product. The mean residence time was increased in this case to comminute the particles to a finer size. Furthermore, a finer feed was predicted to yield a finer product; however, a coarser feed was observed to yield such a product instead. Each hammer milling condition should be controlled with respect to the hammer milling performance and target particle size of the product.